Buy Flexible, Pay More: The Role of Temporary Contracts on Wage Inequality - Andrea Albanese; Giovanni Gallo (Institute of Labor Economics (IZA), 2020)
We investigate the role of temporary contracts in shaping wage inequality in a dual labour market. Based on Italian individual-level administrative data, our analysis focuses on new hires in temporary and open-ended contracts for the period of 2005–2015. To estimate the presence of differentials over the daily wage distribution, we follow Firpo (2007) and implement an inverse probability estimator, which allows us to control for labour market history, including lagged outcomes, over the last 16 years. Our results show the existence of a premium for temporary contracts over the full distribution of daily remuneration at entry, confirming the economic theory of equalizing differences. The wage premium is greater when permanent contracts are more valuable, such as for 'marginalised' categories like female, young, and low-paid temporary workers, and during the years of the economic crisis. The gap remains substantial after taking into account differences in working hours between workers.
Keywords: J31; J41; C31; J21; 330; temporary work; wage inequality; unconditional quantile treatment effect; inverse probability weighting